Commercial Agency Law. - Egypt (2025)
Law No. 120/1982 : Concerning Promulgating Law For Organizing Operations Of Commercial Agency And Certain Mediation Activities. - Chapter : I General provisions - Chapter : II Obligations of commercial agents, mediators and others - Chapter : III Provisions related to contracts concluded by the government and the public sector. - Chapter : IV Regulations of responsibilities and penalties. - Chapter : V Concluding provisions. -- Ministerial Decree No. 342/1982 : The Executive Regulation of law No. 1201982. Chapter : 1 General provisions. - Chapter : 2 On recording in the commercial agents and middlemen register. - Chapter : 3 On the registration of scientific, technical and consultative or other service offices - Chapter : 4 Closing provisions List of documents required for recording of single merchant in the commercial agents and intermediaries register. Form No.(4) Form No. (5) P. D. No. 1906/1974 : Concerning certain provisions related to reorganization of trade agency activities. Law No. 117/1975 : Related to duties of registration in the registers of commercial agency affairs. P.D. No. 14/1976 : Modifying certain provisions of Presidential Decree No. 1906/1974. P.D. No. 107/1961 : Concerning certain provisions organizing trade agency business. – D. No. 1815/1977 : With the procedures of renewal of registration in the commercial agents and services offices registers.— Law No. 93/1974: On citizen's right to act as representatives of foreign firms in the Arab Republic of Egypt. – Ministerial Decree No. 733/1975 : On powers of decision committees.